The synthesis and structures of 1, 1′-bis(sulfonyl)ferrocene derivatives. Issue 36 (19th August 2016) - Chanawanno, Kullapa; Holstrom, Cole; Crandall, Laura A.; Dodge, Henry; Nemykin, Victor N.; Herrick, Richard S.; Ziegler, Christopher J.
Abstract : A series of 1, 1′-bis(sulfonylchloride)ferrocene compounds were synthesized from the corresponding ammonium salt, and converted into either mono or bis sulfonylamides. These compounds exhibit intermolecular hydrogen bonding. Abstract : A series of 1, 1′-bis(sulfonyl)ferrocene compounds were produced via the 1, 1′-bis(sulfonate)ferrocene ammonium salt. This compound can be readily converted to 1, 1′ bis(sulfonylchloride)ferrocene. By varying stoichiometry and reaction times, both mono- and bis-sulfonamide derivatives can be synthesized. All new compounds presented in this report have been structurally characterized. The structures of the bis-sulfonamide systems are similar to the well-studied bis(amide) ferrocene compounds. Intermolecular hydrogen bonding is observed, typically between NH and SO groups of neighboring sulfonamides. However in the bis(GABA) derivative, intermolecular NH to CO hydrogen bonding interactions are present.